Mechanical Properties of a Stability‐Enhancing Honeycomb with Double‐Platform Stresses and Variable Stiffness - Liu, Xu; Liu, Hai‐Tao; Wang, Shun (physica status solidi (b), 2025)
Herein, a stability‐enhancing honeycomb (SEH) is designed based on the diabolo‐shaped honeycomb (DSH). SEH is obtained by adding wedge‐shaped parts to the DSH, which improves the stability of honeycomb deformation. The inclusion of the variable stiffness region imparts variable stiffness properties to the honeycomb. The combined effect of the variable stiffness region and the wedge‐shaped part eliminates the buckling phenomenon during honeycomb deformation. The results demonstrate that the honeycomb generates double‐platform stresses during deformation, and the specific energy absorption (SEA) increases rapidly after entering the variable stiffness region. The effects of the variable stiffness region, wedge‐shaped part, and crossbar length on the mechanical properties of SEH are analyzed using a finite‐element model, which is validated through compression experiments. Adjusting the variable stiffness region changes the strain of the variable stiffness. Modifying the wedge‐shaped part affects the magnitude and corresponding strain of the second plateau stress in the honeycomb. As the length of the crossbar increases, the stress and SEA gradually decrease. This article provides a design concept for variable stiffness honeycombs and offers insights to improve their effectiveness in protective engineering. A stability‐enhancing honeycomb (SEH) is designed. The wedge‐shaped part within the SEH improves deformation stability, and the variable stiffness region achieves the effect of variable stiffness. The effectiveness of the finite‐element model is validated through experiments. The parameters of the variable stiffness region, wedge‐shaped part, and crossbar length are examined.